(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
Analysis of observations and experiments shows that health-improving gymnastics classes for students are an important tool in the development of the younger generation. Exercise is essential for the normal functioning of the body. The great ruler and thinker Abu Ali ibn Sina said, "Physical training is a great way to maintain good health," which is reminiscent of the saying in folk pedagogy, "Whoever does good is blessed."